A novel immunomodulatory function of PHLPP1: inhibition of iNOS via attenuation of STAT1 ser727 phosphorylation in mouse macrophages. Issue 5 (17th January 2014) - Alamuru, Neeraja P; Behera, Soma; Butchar, Jonathan P; Tridandapani, Susheela; Kaimal Suraj, Sasidhara; Babu, P Prakash; Hasnain, Seyed E; Ehtesham, Nasreen Z; Parsa, Kishore V L
Abstract : PHLPP1 inhibited LPS/IFNγ stimulated inducible nitric oxide synthase expression as a novel regulator of macrophage responses. ABSTRACT: PHLPP1 is a novel tumor suppressor, but its role in the regulation of innate immune responses, which are frequently dysregulated in cancer, is unexplored. Here, we report that LPS attenuated PHLPP1 expression at mRNA and protein levels in immune cells, suggesting its involvement in immune responses. To test this, we overexpressed PHLPP1 in RAW 264.7 macrophages and observed a dramatic reduction in LPS/IFN-γ-induced iNOS expression. Conversely, silencing of PHLPP1 by siRNA or by shRNA robustly augmented LPS/IFN-γ-induced iNOS expression. qPCR and iNOS promoter reporter experiments showed that PHLPP1 inhibited iNOS transcription. Mechanistic analysis revealed that PHLPP1 suppressed LPS/IFN-γ-induced phosphorylation of ser 727 STAT1; however, the underlying mechanisms differed. PHLPP1 reduced IFN-γ-stimulated but not LPS-induced ERK1/2 phosphorylation, and inhibition of ERK1/2 abolished IFN-γ-induced ser 727 STAT1 phosphorylation and iNOS expression. In contrast, PHLPP1 knockdown augmented LPS-induced but not IFN-γ-elicited p38 phosphorylation. Blockade of p38 abolished LPS-stimulated phosphorylation of ser 727 STAT1 and iNOS expression. Furthermore, PHLPP1 suppressed LPS-induced phosphorylation of tyr 701 STAT1 by dampening p38-dependent IFN-β feedback. Collectively, our data demonstrate for the first time that PHLPP1 plays a vital role in restricting innate immune responses of macrophages, and further studies may show it to be a potential therapeutic target within the context of dysregulated macrophage activity.